ЖОРСТКІСТЬ МІОКАРДУ У ПРАКТИЧНО ЗДОРОВИХ ЛЮДЕЙ РІЗНОГО ВІКУ - Бодрецька, Л.А.; Шаповаленко, І.С.; Антонюк-Щеглова, І.А.; Бондаренко, О.В.; Наскалова, С.С. (Українські медичні вісті, 2023)
ЖОРСТКІСТЬ МІОКАРДУ У ПРАКТИЧНО ЗДОРОВИХ ЛЮДЕЙ РІЗНОГО ВІКУ